Expression of flagellin FLjB derived from Salmonella enterica serovar typhimurium in Escherichia coli BL21 - Huyen, Do Thi; Giang, Le Quynh; Hai, Truong Nam (Academia Journal of Biology, 2015)
Flagellin FljB composes flagellar antigen (H:1,2) of S. Typhimurium. This kind of antigen increases immunogenicity of any conjugated antigen upon administration. Thus, it is supposed to have an enormous potentiality for vaccine development against bacterial infections and cancer diseases. fljB gene (1515 nucleotides) coding for mature FljB was amplified by PCR from genomic DNA of S. Typhimurium and inserted into pET32a(+) for expression in E. coli BL21. The protein FljB was well expressed under the fusion form with Trx, S-tag at N terminal and hexa-histidine at C terminal, thus the recombinant protein was abbreviated to TrxFljB. Study on the impact of temperature on the gene expression showed that TrxFljB was synthesized at lower level at 37oC comparing to the levels at 22oC and 25oC. 13% of the protein synthesized at 37oC was inclusion body. Lower temperatures used during induction phase increased the solubility of the recombinant protein. About 97% of TrxFljB synthesized at 25oC was soluble. IPTG concentration had a strong effect on the growth of freshly transformed cells but did not affect on the growth of stored and re-cultivated cells. The increase of IPTG concentration resulted in the decrease of the growth of freshly transformed cells and the TrxFljB productivity. However, 0.05 mM IPTG concentration was found to gain the full TrxFljB expression. TrxFljB productivity declined during storage of cells at 4oC and re-cultivation. At optimal condition, volumetric productivity of TrxFljB was about 300 mg/ l broth.